Analysis of multiple‐TX WPT systems using KVL and RX‐side RLT. Issue 12 (29th July 2019) - Zhang, Jin; Cheng, Chonghu; Chen, Kai; Wang, Fangfang; Gao, Yingjie
Abstract : Wireless power transfer (WPT) system with multiple transmitters (TXs) and one receiver (RX) can effectively enlarge the range of power transmission region. The power delivered to load (PDL) and power transfer efficiency (PTE) of two‐TX WPT system has been intensively studied in the past few years. To achieve a wider range of power transmission, the multiple‐TX system should be investigated urgently. Using Kirchhoff's voltage law (KVL) and RX‐side reflected load theory (RLT), this study analyses a general multiple‐TX and single‐RX systems in detail. The explicit closed‐form equations for the highest PDL, PTE and corresponding optimal loads are derived from the two methods. The constraint of feeding amplitude ratios need be equal to the mutual inductance ratios for the highest PTE deduced from KVL; on the other hand, inspired by TX‐side RLT using in the multiple‐RXs system, RX‐side RLT is first proposed and can readily derive the highest PDL, PTE and optimal loads compared with KVL. Numerical simulations for three‐ and four‐TX systems are implemented to intuitively illuminate the theoretical analysis. Experiments for two‐, three‐ and four‐TX systems have verified the accuracy of the proposed analysis.